2013
DOI: 10.4028/www.scientific.net/amm.371.28
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Lubrication Method and the Cutting Regime on the Surface Roughness when Milling 7175 Aluminum Alloy

Abstract: In the current paper, some aspects regarding the quality of the surface machined under different lubrication conditions is being assessed: cutting under a jet of cutting fluid, minimum quantity lubrication cutting, dry cutting. The objective was to assess the results obtained after MQL cutting in comparison with dry cutting and cutting under a jet of cutting fluid. The variables of the cutting regime were the feed rate and the type of milling (climb and conventional). This study has an important ecological imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Due to the adhesive property of aluminium, grinding can be challenging as any chips generated tend to clog the grinding wheel [89]. Contrary to the good surface quality reported in milling experiments [61], the surface quality of AA6061 aluminium alloy in MQL grinding was found to be unsatisfactory with the surface roughness being between that of conventional flood cooling and dry grinding. Furthermore, under lower removal rates it was observed that the surface quality obtained from dry grinding surpassed that of MQL [37].…”
Section: Grinding Of Aluminiummentioning
confidence: 89%
See 1 more Smart Citation
“…Due to the adhesive property of aluminium, grinding can be challenging as any chips generated tend to clog the grinding wheel [89]. Contrary to the good surface quality reported in milling experiments [61], the surface quality of AA6061 aluminium alloy in MQL grinding was found to be unsatisfactory with the surface roughness being between that of conventional flood cooling and dry grinding. Furthermore, under lower removal rates it was observed that the surface quality obtained from dry grinding surpassed that of MQL [37].…”
Section: Grinding Of Aluminiummentioning
confidence: 89%
“…This was confirmed by Tsao who investigated the milling of A6061P-T651 aluminium alloy [59] where it was noted that the application of sulphurous boric acid Apart from tool wear reduction, the surface quality of the workpiece was found to be improved under MQL conditions. Diciuc and colleagues studied the effect of different lubrication methods (MQL, flood cooling and dry) on the surface roughness of a milled 7175 aluminium alloy workpiece [61]. Based on the experimental results, the lowest surface roughness value -11 -was achieved under MQL conditions in low (118 mm/min to 170 mm/min) and high (268 mm/min to 375 mm/min) feed rates.…”
Section: Turning and Milling Of Aluminiummentioning
confidence: 99%